Androgen receptor expression in hypospadias - Dhanvanth Rajesh Balaji; Goutham Reddy; Ramesh Babu; Balamourougane Paramaswamy; Madhu Ramasundaram; Prakash Agarwal; Leena Dennis Joseph; Lawrence D'Cruze; Sandhya Sundaram (Wolters Kluwer Medknow Publications, 2020)
Introduction: The exact mechanism behind the development of hypospadias is unclear. Research studies on androgen receptor (AR) expression are controversial with results stating all possible outcomes - AR elevated, similar, or reduced when compared to normal. Aims: The aim is to study the AR expression and hormone levels in hypospadias patients and compare them with children having normal genitalia. Methods: Group 1 (controls) involved patients who underwent circumcision for phimosis while Group 2 involved hypospadias patients who did not receive any preoperative testosterone. Preoperative hormonal assay included luteinizing hormone, follicle-stimulating hormone, and free testosterone levels in all the patients. The foreskin specimen was analyzed for AR expression using immunohistochemistry (anti-AR antibody PathnSitu, clone R441, 1/100 dilution). AR staining was expressed as H score. The H score was calculated by multiplying the intensity of staining and the percentage of stained cells showing cytoplasmic positivity at high power (×40). Results: There were 27 patients in Group 1 while 16 in Group 2 (distal 10; proximal 6).There was no significant difference in the age distribution. The mean H score was significantly higher (189.5) in hypospadias patients compared to controls (97.5) and was significantly higher in proximal (220) compared to distal (159) hypospadias. There was no significant difference in hormone levels between groups. Conclusion: AR expression was significantly elevated in hypospadias patients. It was higher in proximal compared to distal hypospadias, probably due to end-organ overexpression. Further larger trials are likely to through light into this controversial subject.